SIMULATION AND EXPERIMENTAL WORK OF KINEMATIC PROBLEMS FOR KUKA KR 5 SIXX R650 ARTICULATED ROBOT - Sulaiman , Marizan; Syaffiq, MIK; Shah, HNM; Fakhzan, MN (UMPEDAC, University of Malaya, 2013)
This paper studies an analytic solution for 6-DOF manipulator of a KUKA KR 5 SIXX R650 robotic arm using forward and inverse kinematics in a simple movement process. This paper proposes two points of movement in order to study three types of path motion used in the robotic arm. The three path motions are PTP (point-to-point), linear and circular. The motions are analyzed systemically using forward kinematics and inverse kinematics. The objective of forward kinematic analysis is to determine the cumulative effect of the entire set of joint variables. A simulation oriented analysis is obtained and comparison between simulation and experimental result is done. The result for both simulation and experimental works show close connection for the task. This robot is suitable to be applied to the teaching and training environment.